Marca na mão: como desenvolver um aplicativo eficaz para gerar engajamento com seus clientes. - Meira, Juliana de Albuquerque (2021)
This research addresses the theme of mobile applications, based on the concept of mobile marketing applied to the coffee shop segment. The research started from the following problem: how do brands use mobile applications to engage consumers? To operationalize the investigation, the coffee segment was adopted for a case study, more specifically the cases of Starbucks, São Braz, Suplicy and Fran´s Café. Considering the objectives of this dissertation, the comparative method (MC) was used. Thus, it was possible to compare differences and similarities between the applications of the three cases investigated. Content analysis was also used as a methodological resource to compare the functionalities of the applications. We live in a connected world, and more and more communication takes place through the use of smartphones. Therefore, the strength of this tool provided by the advancement of technology is undeniable. This is the defense of some authors. With the realization of this research, an overview was obtained about how Brazilian coffee shops use mobile applications in their business strategy and how they are built in comparison to the main application in the segment, leading to an ideal application model. This work also made possible the elaboration of its own model that presents the important resources to be considered in an effective application. From this model, a prototype of an ideal cafeteria application was created that includes tools and resources to obtain better results in terms of customer relationship.